Islamistische Radikalisierung: Ein Überblick über Verbreitung, Definitionen, Erscheinungsformen, Ursachen und Handlungsansätze - Veronika Zimmer; Margit Stein; Mehmet Kart; Eike Bösing; Caner Ayyildiz; Yannick von Lautz (IU Internationale Hochschule, 2022)
– This article provides an overview of the prevalence, definitions, manifestations and causes of Islamist radicalisation as well as possible approaches to counteracting it preventively and interventively. First, an overview is given of the potential of Islamist radicalised persons in Germany. The estimate is made on the basis of an overview of radical groups with an Islamist orientation and their potential number of persons. Overall, the difficulty in estimating the number of radicalised people is also due to the fact that it is difficult to define and clearly delimit the concept of Islamist radicality or radicalisation as well as Islamist extremism or terrorism. In a second large block, the course of radicalisation is traced using different models, but theoretical explanations for radicalisation are also presented. Overall, the causes are located at the micro level (such as personality traits, identity conflicts), the meso level (such as family and friendship socialisation experiences) and the macro level (such as Islamophobia and racism). In the presentation of the approaches against Islamist radicalisation, a special focus is placed on the importance of Islamic religious education. This is also the focus of the UWIT project, which asks lecturers and students at the Institutes of Islamic Theology about their assessments of how teaching can have a preventive effect.
urn:nbn:de:101:1-2022020912190844372042
Keywords: 300; Islam; radicalization; extremism; terrorism; religious education; school; teachers; prevention